(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the changes in ferritin, transferrin, and serum iron concentrations in cirrhosis patients and analyze the relationship between changes in transferrin, serum iron and ferritin with the severity of cirrhosis according to the Child - Pugh score. Subject and methods: 80 patients with cirrhosis treated at Thai Nguyen Central Hospital were divided into 3 groups: cirrhosis caused by virus B or/and C, cirrhosis caused by alcohol, cirrhosis combined with alcohol and virus B or/and C. Cross-sectional descriptive study. Results: Serum ferritin concentrations in all 3 groups caused by viruses, alcohol abuse, and the group caused by alcohol and viruses were mainly at normal and high levels, with almost no ferritin at low levels (p>0.05). Serum iron concentration in Child Pugh A group was higher than Child Pugh B and C. Serum ferritin concentration increased in Child Pugh B and C groups higher than Child Pugh A. Transferrin concentration in all 3 groups decreased (p>0.05). Serum transferrin concentration in Child Pugh A group was higher than Child Pugh C, and was lowest in Child Pugh C Conclusion: Cirrhosis patients often have decreased serum iron and transferrin and increased ferritin.